The Effectiveness of the POGIL Learning Model on Simple Harmonic Motion Topic to Enhance Students' Science Process Skills - Nor Aulida Rahmi; Dewi Dewantara; Mastuang Mastuang (Jurnal Ilmiah Pendidikan Fisika, 2024)
The lack of training in students' science process skills indicators in physics subjects has resulted in a majority of students in one of the high schools in Banjarmasin, grade X MIPA, having relatively low science process skills. This study aims to describe the effectiveness of the POGIL learning model and assess the achievement of students' science process skills. This study used a one-group pretest-posttest design. The results showed that using the POGIL model based on the n-gain calculation had a high effectiveness category with a value of 0.73 and trained students' science process skills, as indicated by an increase in the achievement of science process skills, which had a very good category. Based on these results, using the POGIL model can provide benefits in practicing students' science process skills.